2015
DOI: 10.1155/2015/172862
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Polymeric Fluids in Strong Stress Fields

Abstract: Analysis of literature data and our own experimental observations have led to the conclusion that, at high deformation rates, viscoelastic liquids come to behave as rubbery materials, with strong domination by elastic deformations over flow. This can be regarded as a deformation-induced fluid-to-rubbery transition. This transition is accompanied by elastic instability, which can lead to the formation of regular structures. So, a general explanation for these effects requires the treatment of viscoelastic liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Now, the role of viscoelasticity is included in theoretical and experimental examination [ 155 , 156 ]. Just the elasticity should be considered the driving mechanism for the emergence of deformation-induced regular structures including such as a bead-on-string formation [ 157 ]. The experiments showed that by varying rheological properties of polymer solutions, it is possible to realize transition from capillary to viscoelastic instability [ 158 ] and from the elasto-capillary mechanism of instability to phase separation [ 159 ].…”
Section: Deformation-induced Structure Effects In Solutionsmentioning
confidence: 99%
“…Now, the role of viscoelasticity is included in theoretical and experimental examination [ 155 , 156 ]. Just the elasticity should be considered the driving mechanism for the emergence of deformation-induced regular structures including such as a bead-on-string formation [ 157 ]. The experiments showed that by varying rheological properties of polymer solutions, it is possible to realize transition from capillary to viscoelastic instability [ 158 ] and from the elasto-capillary mechanism of instability to phase separation [ 159 ].…”
Section: Deformation-induced Structure Effects In Solutionsmentioning
confidence: 99%